Pengaruh Sosialisasi Media Ruang KPU Kota Pematangsiantar terhadap Minat Kelompok PEMILU pada PEMILU Legislatif - samosir, Rudi (JUPIIS: Jurnal Pendidikan Ilmu-ilmu Sosial, 2015)
The aims of this research are to understand the forms of socialization held by General Election Commission (KPU) of Pematangsiantar City; to understand the communication channels conducted by KPU of Pematangsiantar City for socialization; to understand the factors affecting voters for electing; and to understand effect of socialization of spatial media of general election by General Election Commission of Pematangsiantar City in 2014 in Pematangsiantar City. The research method using in the research is correlation method. Population of the research is participant of socialization held by KPU of Pematangsiantar City. Its amount is 615 respondent. Technique for electing the sample in this research uses technique of slovin. Sample of the research amount of 85 respondent. Technique of collecting data in the research uses technique of questionnaire. The result of this research shows the forms of socialization held by KPU of Pematangsiantar City in legislative general election of 2014 is by using method of group communication. Communication channel which was used by KPU of Pematangsiantar City for socialization on the Legislative General Election of 2014 is by using direct communication (face to face). The factors are affecting the voters interest on 2014 General Election in Pematangsiantar City is language style which is used in socialization, frequency in accepting the message of general election by respondent after socialization and timing which is needed by KPU in conveying socialization matters.